2012
DOI: 10.1128/jvi.06274-11
|View full text |Cite|
|
Sign up to set email alerts
|

Cholesterol-Rich Microdomains as Docking Platforms for Respiratory Syncytial Virus in Normal Human Bronchial Epithelial Cells

Abstract: Respiratory syncytial virus (RSV) is one of the major causes of respiratory infections in children, and it is the main pathogen causing bronchiolitis in infants. The binding and entry mechanism by which RSV infects respiratory epithelial cells has not yet been determined. In this study, the earliest stages of RSV infection in normal human bronchial epithelial cells were probed by tracking virions with fluorescent lipophilic dyes in their membranes. Virions colocalized with cholesterol-containing plasma membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 93 publications
(98 reference statements)
1
63
0
1
Order By: Relevance
“…1). This internalization occurs when the RSV envelope fuses with the host cell at or near the plasma membrane on lipid raft platforms (96), and fusion is triggered in a pH-independent manner. There was a recent report showing that prior to fusion, RSV is internalized in an actin-dependent process called macropinocytosis which also appears to require the host cell protein Rab5 in HeLa cells (95).…”
Section: Entry Of Rsv and Its Host Cell Receptorsmentioning
confidence: 99%
“…1). This internalization occurs when the RSV envelope fuses with the host cell at or near the plasma membrane on lipid raft platforms (96), and fusion is triggered in a pH-independent manner. There was a recent report showing that prior to fusion, RSV is internalized in an actin-dependent process called macropinocytosis which also appears to require the host cell protein Rab5 in HeLa cells (95).…”
Section: Entry Of Rsv and Its Host Cell Receptorsmentioning
confidence: 99%
“…Particularly, the respiratory syncytial virus (RSV), which causes respiratory infections in children, binds to cholesterol-rich lipid rafts in the plasma membrane of human bronchial epithelial cells [30]. Moreover, the release of RSV virus particles from infected cells also requires cholesterol-rich lipid rafts [31].…”
Section: Introductionmentioning
confidence: 99%
“…First, we investigated whether depletion of cellular cholesterol by Gem and Lov inhibits virus entry process in human airway cells, because a previous study suggested that lipid raft serves as an entry platform for RSV (San-Juan-Vergara et al, 2012). Cells treated with Gem (400 μM) and Lov (40 μM) for 24 h were infected with the viruses at MOI of 0.5 for 24 h. Cells were then fixed and the number of infected cells were determined by immunostaining using specific anti-NP monoclonal antibodies (mAb).…”
Section: Resultsmentioning
confidence: 99%
“…These results highlighted the difference in requirement of raft integrity for virus budding and release among respiratory RNA viruses. All of these enveloped viruses are known to utilize ordered lipid raft domains to localize essential viral components during assembly (Nayak et al, 2009; Nayak et al, 2004; Oomens et al, 2006; San-Juan-Vergara et al, 2012). Cholesterol seems to be required for cell surface accumulation of SeV and hPIV1, but not for IAV and RSV glycoproteins (Fig.…”
Section: Discussionmentioning
confidence: 99%